Improvement of Curvature Change Rate (Parameter) in Two-Line Rural Roads - Lina Bertulienė; Romas Girdvainis; Lina Juknevičiūtė-Žilinskienė; Vilimas Gintalas (The Baltic Journal of Road and Bridge Engineering)
The studies in various countries show that one of the main causes of accidents on rural roads still remains the drivers’ errors in choosing safe speed, which can be attributed to the errors of perceiving the road alignment. The current practice shows that the engineering safety improvement measures as well as accident prevention measures such as intersection design, traffic signs and equipment, facilities for vulnerable road users, access management, and human behaviour are not always effective. Probably, one of the alternatives to solve this problem is a design methodology that is used in the European Union countries and based on road safety criteria and road safety module. This methodology is aimed at ensuring design consistency between the elements of road alignment in a way that the driver intuitively chooses safe speed or the probability of errors in perceiving the road alignment is minimum. The article presents experimental research carried out in Vilnius Gediminas Technical University, the objective of which is to determine the accuracy of road safety module and to suggest possible alternatives for its improvement.